Gambaran Histologi Gonad Ikan Nila (Oreochromis niloticus) dengan Pemberian Terong Rimbang (Solanum torvum) dalam Pakan - Lisa Fandana; Azwar Thaib; Teuku Ridwan; Nurhayati Nurhayati (Jurnal TILAPIA, 2020)
Tilapia is one of the economically valuable freshwater fishery commodities, the development of tilapia aquaculture continues to increase, premature sex maturity often occurs in tilapia when the enlargement process is mixed between male and female sexes. Eggplant wavers (Solanum torvum) is one of the plants that can be used to inhibit the reproduction process because it contains sterol carpesterol and solasodine compounds. This study aims to determine the Gonad Maturity Index in male and female tilapia and the development of spermatogenesis in male tilapia. The experimental design used was a non factorial Complete Randomized Design (CRD) with 3 treatments and 4 replications. As treatment includes treatment A (control), treatment B (50 grams of eggplant weight), and treatment C (100 grams of eggplant weight) mixed in feed. The results showed that the addition of balanced eggplant in the feed to the IKG did not show differences between treatments, while the results of histological tests on spermatogenesis gave a positive trend in inhibiting microscopic testicular tilapia cells.